Characterization Methodology of a Tribological Couple: Metal Matrix Composite/Brake Pads - Sallit, I.; Richard, C.; Adam, R.; Robbe-Valloire, F. (Materials characterization, 1998)
Industry wishes to develop more efficient materials for use in severe and complex conditions. Thus, not only are new materials continually developed, but also a better understanding of these materials is sought. In the car-making industry, any reduction in the weight of moving parts lowers the level of vibration and fuel consumption, leading eventually to a more efficient vehicle. The properties of metal matrix composites (MMCs), such as increased wear and temperature resistance, as well as low density, have been the subject of many studies. The authors are especially interested in the study of the coupling of MMCs with hypereutectic alloys composing brake disks/brake pads. Brake disks are usually made of cast iron and are one of the moving parts that can gain in efficiency if they are lightened. This study was carried out to define a characterization methodology, so as to identify the wear mechanisms of this tribological couple, and to evaluate the behavior of these new materials. One of the features of this couple is the constitution of a transfer layer on the disk, because this has an important effect on the behavior of this couple. Through the following characterization methodology, some wear mechanisms will be studied.